Aeromycological study of Chandragiri hill top, Chhattisgarh - Chelak, Eeshwary Prasad; Sharma, K (International Multidisciplinary Research Journal, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]--> Aeromycoflora of Chandragiri Hill Top was studied with the help of Petriplate method. Total 275 fungal colonies represented 28 fungal species were observed during the present investigation period. Environmental factor play an important role for the distribution of the fungal spores. Out of 28 fungal types, Maximum numbers of fungi (24) were isolated from anamorphic group, (03) from Ascomycotina and minimum (01) from Zygomycotina. The fungal species were Cladosporium oxysporium, Fusarium Mycelia sterilia, Aspergillus, Penicillium, Curvularia, Cladosporium, Rhizopus ,Trichoderma species were observed. It is found that maximum percentage contribution is observed for Cladosporium oxysporium, followed by Aspergillus niger, A. Versicolor, A fumigates. On the contrary, minimum percentage contribution is observed for Aspergillus terreus.